Sense of community and the built environment the role of the physical environment on the person-place relationships in the context of residential communities in Davao City - Sabate, Joshua Miguel V. (2013)
Sense of community can be defined as the level of belonging, connection, and support that people feel in their community. The presence of sense of community in urban neighborhoods has been shown to help create healthy communities and increase psychological well-being among its members. The purpose of the study was to find psychological, and more importantly, physical factors facilitating perception of community. District aspects of the physical environment were examined through surveys with 3 low-cost to middle-class communities in Davao City. The findings suggest that La Verna Heights residents perceive substantially greater sense of community; they express strong sense of identity with their community, connection to their neighbors, and attachment to their community. On street parking, presence of community court, residential density, street trees and landscaping, and street width played particularly important roles in sense of community, fostering community attachment & identity and increasing likelihood of social interactions. An existential-phenomenological approach or the systematic interpretation of other people?s experiences sought to understand the specified people-place relationships in their community. The design of the public/private realms, the provision of spaces of interaction and the degree of control to these spaces emerged as primary design factors for social interaction. The proximity of housing units and streetscape design were also found coherently affecting sense of community.